2007
DOI: 10.1007/s11064-007-9286-0
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin in Cerebrospinal Fluid: Age-related Reference Values and Relevance in Neurological Disease

Abstract: We aimed to establish age-related reference values for Erythropoietin (EPO) in cerebrospinal fluid (CSF) and to evaluate concentrations in neurological diseases. CSF and serum EPO was measured in controls with tension-type headache (CTTH), in patients with ALS, dementia and depression using ELISA technique. Stability experiments showed CSF EPO to be stable for two and a half months and over two thaw/freeze cycles. A positive correlation of CSF EPO with age was found (P<0.01). We found a CSF/serum EPO concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…No analyses were performed on long-term, frozen archival plasma/CSF samples. Retrospective analysis of Epo protein in archival CSF samples from these patients was not performed since growth factors such as Epo only survive in frozen CSF for less than three months [32]. …”
Section: Methodsmentioning
confidence: 99%
“…No analyses were performed on long-term, frozen archival plasma/CSF samples. Retrospective analysis of Epo protein in archival CSF samples from these patients was not performed since growth factors such as Epo only survive in frozen CSF for less than three months [32]. …”
Section: Methodsmentioning
confidence: 99%
“…Initial studies focused on the expression levels of EPO in cerebrospinal fluid, serum, and plasma of ALS patients. Studies demonstrated a decrease of EPO levels in ALS patients’ cerebrospinal fluid but not in patients’ serum (Brettschneider et al., 2007; Widl et al., 2007). Further studies indicated that EPO levels were decreased in the plasma of only a subset of ALS patients, which are those that presented with respiratory failure (Carilho et al., 2011).…”
Section: Epo’s Implications In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Expression of EPOR has also been detected on myelin sheath of radicular nerves and in the epineurial blood vessels of sural nerves in the human peripheral nervous system [161,162]. Measurements of endogenous levels of EPO in CSF of patients with neurodegenerative diseases has revealed EPO in CSF of patients with ALS to be lower than in controls whereas patients with Alzheimer disease (AD) or vascular dementia had EPO levels comparable to control persons [163,164]. Astrocytic EPOR immunoreactivity in postmortem hippocampus and temporal cortex from subjects with AD or chronic schizophrenia has been reported to be increased as compared to age-matched control brains [119,158].…”
Section: Translation To Human Brain Diseasementioning
confidence: 99%